2008
DOI: 10.1897/08-157.1
|View full text |Cite
|
Sign up to set email alerts
|

Protectiveness of species sensitivity distribution hazard concentrations for acute toxicity used in endangered species risk assessment

Abstract: A primary objective of threatened and endangered species conservation is to ensure that chemical contaminants and other stressors do not adversely affect listed species. Assessments of the ecological risks of chemical exposures to listed species often rely on the use of surrogate species, safety factors, and species sensitivity distributions (SSDs) of chemical toxicity; however, the protectiveness of these approaches can be uncertain. We comprehensively evaluated the protectiveness of SSD first and fifth perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…In the same study, compilation and analysis of experimental values indicated that intraspecific variability could be a significant source of uncertainty in species sensitivity distribution (SSD). In another study, experimental Daphnia acute toxicity figures varied by up to 60-fold for the 10 evaluated chemicals, and even highly standardized datasets showed greater than 10-fold differences [26]. In our test set, we noticed a similar situation: experimental acute toxicity values in our test set varied …”
Section: Resultssupporting
confidence: 69%
“…In the same study, compilation and analysis of experimental values indicated that intraspecific variability could be a significant source of uncertainty in species sensitivity distribution (SSD). In another study, experimental Daphnia acute toxicity figures varied by up to 60-fold for the 10 evaluated chemicals, and even highly standardized datasets showed greater than 10-fold differences [26]. In our test set, we noticed a similar situation: experimental acute toxicity values in our test set varied …”
Section: Resultssupporting
confidence: 69%
“…Recently, interspecies correlation estimates (ICE) have been used to predict toxicities of nontested invertebrates and fish with great accuracy. ICE may become especially valuable because it provides a prognostic tool to obtain a suite of taxa sensitivities that have different physiological and ecological traits (Dyer et al 2006Raimondo et al 2008).…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…For example, ERA for birds and mammals extrapolate toxicity data for rats or quails (standard test species) to voles and sky larks (focal species) by the use of assessment factors. Other approaches are also available for this extrapolation, such as species sensitivity distributions (Newman et al 2000, Raimondo et al 2008) and interspecies correlation estimation (Raimondo et al 2010). It may also be possible to predict the intrinsic sensitivities of specific fish to a toxicant by combining toxicokinetic–toxicodynamic models (Ashauer and Escher 2010, Stadnicka et al 2012) and in vitro screening techniques (Segner et al 2003).…”
Section: Discussionmentioning
confidence: 99%